Mini Proposal Rencana Strategis PT. SolarTech Indonesia Perusahaan Manufaktur Solar Panel - Indriyani Putri, Afifah; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Renewable energy is a strategic solution to overcome the problem of limited fossil fuel sources and the negative impacts of climate change. This study discusses the potential and challenges of developing solar panel technology as a source of clean energy in Indonesia, a tropical country with abundant sunlight potential. This study uses a SWOT analysis approach to PT. SolarTech Indonesia, a solar panel manufacturing company, to evaluate the strengths, weaknesses, opportunities, and threats in the renewable energy industry. The results of the analysis show that although initial investment and dependence on weather conditions are obstacles, large market opportunities and government policy support provide significant growth potential. The strategy of developing technological infrastructure, increasing public awareness, and synergy with stakeholders are the keys to the company's success in supporting sustainable development goals (SDGs) related to clean energy. This study recommends strengthening collaboration and technological innovation as a step forward to accelerate the energy transition in Indonesia.